Developing A 2-Dimensional (2D) animation techniques for CD-I recognizing Islamic figure - Irma Shayana, Samaden; Muhammad Edzwan, Zahri (IDOSI Publications, 2017)
This paper discusses about the process of 2-dimensional animation techniques for CD-Interactive (CD-I) recognizing Islamic figure in e-learning bases. The contents in this application is based on actual historical information that been have summarized in addition to their quiz to attract the target audient. The objective is to gain children’s interest to know and learn the history of Islamic figure. In general, when we use on CD-I application which gives more positive impact on e-learning especially for children was aged 10-17 years old. This element may provide a significant contribution to the process of the formation of the younger generation personality than of its contribution in the field of education. In this application, we also have combined the ADDIE Model with element of multimedia. For conclusion, hopefully with this application is to make the target audient become more interested, more motivation to explore, learn something about the figure and makes it a reference in exploring their life.